De princesas a esclavas. En Troya. (Heroínas de la mitología griega III) - Esteban Santos, Alicia (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
This paper deals again with the Trojan women, but now focussing on their essencial change of social and personal status, because all of them —even the queen and the princesses— became slaves, and concubines of men who had killed their family and destroyed their city. We talk about Briseis, Chryseis, Tecmessa, Hecuba, Polyxena, Andromache and Cassandra —and also about Hesione— and we can see important analogies and oppositions between them, especially with regards to their respective attitude, submissive or rebel.